Amamistatins isolated from Nocardia altamirensis - Steinmetz, Till; Hiller, Wolf; Nett, Markus (Beilstein Journal of Organic Chemistry, 2022)
Four new phenolic siderophores were isolated from the actinomycete Nocardia altamirensis along with the known natural product amamistatin B and a putative biosynthetic shunt product. The structures of all compounds were elucidated through 1D and 2D NMR analyses as well as mass spectrometry. The iron-chelating properties of the retrieved metabolites were evaluated in a chrome azurol S assay.
Keywords: actinomycete; amamistatin; Nocardia; siderophore; structure elucidation